Structural and Functional Rearrangement of Great Arterial Vessels in the Late Postresuscitative Period - I. V. Mukhina; R. S. Kulikov; Ye. I. Yakovleva; N. N. Andreyeva; N. N. Prodanets; L. B. Snopova; M. L. Bugrova (Общая реаниматология, 2007)
Objective: to study the specific features of remodeling of the aorta, carotid, and femoral artery in the late postresuscitative period.Materials and methods. Experiments were carried out on non-inbred albino rats when clinical death was stimulated by the method of V. G. Korpachev due to 10-minute cardiovascular fascicle ligation. Before clinical death and 60 days after resuscitation, blood pressure, vascular tissue malonic dialdehyde levels, and plasma biochemiluminescence parameters were recorded and great vascular tissue microscopic and ultramicroscopic studies were conducted.Results. On day 60 following resuscitation, a unitary connective tissue carcass was shown to form in the great vascular intima and media via chaotic synthesis of heretodirection-al fibers. This appeared as elevated levels of collagenous fibers in the intima and media as shown by light microscopy. The aortic, carotid, and femoral arterial media displayed a large number of secreting smooth muscle cells and elevated levels of collagenous fibers, which was an active vascular wall remodeling process. Enhanced free radical processes during reperfusion both in the whole organism and vascular wall tissue were one of the triggers of remodeling processes after ischemia. Impaired vascular tone regulation caused by the development of vascular wall remodeling by the connective tissue vegetation growth type contributed to the development of a hypertensive response in the late period. Conclusion. The late postresuscitative period was marked by increased connective tissue in the media of great vessels, by imperfect recovery of the morphofunc-tional status of the endothelial lining, which was likely to be a cause of increased vascular stiffness and elevated blood pressure in rats 2 months after resuscitation.